Analyse Discriminante Des Difficultes D’apprentissage En Milieu Universitaire : Cas Des Etudiants De La Filiere Des Sciences Economiques Et De Gestion De l’UM5R - Radi, Saïd; Bahyaoui, Salwa (European Scientific Journal, ESJ, 2017)
In a context of massification, students of open access programs in higher education encounter more learning difficulties than their counterparts of the regulated system. In the educational literature, these learning difficulties are mainly explained by deficiencies attributable to the students; their perception is seldom taken into account. This led us to explore such difficulties from the learner’s point of view in an unregulated system, namely the economics and management courses of the Mohammed V University in Rabat. This exploration was based on a discriminant analysis conducted on a sample of 122 students. The results of this study, while confirming the important role of the student’s behavioral and metacognitive commitment in the learning process, emphasize the deficiencies of the institution and the professors that also explain a main part of learning difficulties. They also highlight the lack of accompaniment of learners from their pupil status to that of students which reveal the early appearance of these difficulties.